A practical guide to the supportive and palliative care of patients with chronic kidney disease - Paget, Graham; Rekhviashvili, Vakhtang (African Journal of Nephrology, 2020)
We are sure that all of us involved in the field of renal medicine in South Africa would agree that the guidelines, published on page 86 of this issue, around the supportive care of renal patients, especially those who cannot access renal replacement therapy – produced in collaboration between the South African Renal Society and the Association of Palliative Care Practitioners of South Africa – will prove valuable in assisting us in making difficult decisions and in providing constructive advice on the management of our patients with advanced chronic kidney disease (CKD). South Africa’s GDP per capita, of around US3600, places it within the upper-middle-income economic group. Unfortunately, our economy must cope with limited resources with the burden of both non-communicable and communicable diseases. We have one of the highest prevalences of HIV infection in the world, with high frequencies for the APOL1 G1 and G2 risk alleles for HIV-associated (and other) nephropathies [1]. The World Health Organization’s Global Health Observatory (https://www.who.int/data/gho) reports the crude prevalence of hypertension in South Africa at 24%, diabetes at 9.8%, overweight at 51.9% and physical inactivity at 37.2%. The South African Renal Registry [2] reports that 84% of South Africans rely on state-funded medical facilities. A metaanalysis by Kaze et al. [3] quotes the prevalence of CKD stages 3 to 5 to be around 4.8% of the population in sub-Saharan African countries, and in South Africa this amounts to some 2.7 million people with significant kidney disease. Considering our risk profile for renal disease, this is unlikely to be an overestimate. According to the renal registry, only around 11 000 individuals in South Africa are on dialysis or have functioning kidney transplants, with 3100 served by the public sector. Unfortunately, our transplantation rate is low – 4.8 pmp in the public sector and 15.2 pmp in the private sector between 1991 and 2015 [4]. Transplant centres in the UK reported adult deceased donor renal transplant rates between 24 and 66 per million population in 2018/19 [5]. We have large numbers of individuals with end-stage renal disease (ESRD), who are on a palliative care path, not by choice, and this is distressing. These guidelines should not be a substitute for ongoing efforts by our government to “move as expeditiously as possible towards the full realisation of the right to healthcare services”, as enshrined in Section 27 of our constitution. We congratulate our nephrology and palliative care community, and thank our visiting Australian colleagues, for well thought out and practical guidelines, which cover all aspects of supportive care for ESRD patients, including effective and caring communication, symptom management, preserving renal function, end-of-life care, care of paediatric patients, and models for setting up a renal palliative care service. The South African Essential Drugs List was used where possible to ensure that the medications are universally available in South Africa. Graham Paget and Vakhtang Rekhviashvilli South African Renal Society [see PDF file for references]